Strategy for sustainable and green chromatographic separation science: innovation, technology and application - Khan, Mohammad Sharif; Azmir, Jannatul; da Silva Junior, Ademario Iris; Yong, Foo Wong; Mollah, Mamun; Alam, Mohammad Khairul; Althakafy, Jalal T.; Sarker, Md. Zaidul Islam (Bentham Science, 2020)
Green separation science involves extraction, pre-concentration and chromatographic analysis aiming at minimizing environmental impact by reducing energy and reagent usage and reducing or eliminating waste generation. However, the enrichment of trace analytes and/or the analysis of complex matrices most frequently require several steps before analysis, such as extraction, pre-concentration, clean up and preparative chromatography. Thus, alternative and greener separation techniques and solvents are replacing classical methods to diminish the carbon footprint and increase sustainability. Moreover, many innovations are also emerging to curtail the environmental impact of samples analysis; such as micro or nano analytical platforms, sensor-based systems and direct injection to high-resolution mass spectrometry. The current review provides an updated account of the green and sustainable separation science techniques. The current innovations on greener separations and their application in different fields of study are discussed.